Subject of interrogation minor suspect at investigation of thefts, persons accomplished by a group - Манжос, І. О. (Problems of legality, 2013)
The features of the subject of interrogation minor suspect at investigation of thefts, persons accomplished by a group are considered. Determined and summarized the circle of circumstances, that is included in the subject of interrogation minor and the blocks of questions, that is subject to finding out, are distinguished.